Impacts of fuel feeding methods on the thermal and emission performance of modern coal burning stoves - Ahmad, Riaz; Zhou, Yuguang; Zhao, Nan; Pemberton-Pigott, Crispin; Annegarn, Harold John; Sultan, Muhammad; Dong, Renjie; Ju, Xinxin (International Journal of Agricultural and Biological Engineering, 2019)
The extensive use of traditional cooking and heating stoves to meet domestic requirements creates a serious problem of indoor and outdoor air pollution. This study reports the impacts of two fuel feeding methods – front-loading and top-loading on the thermal and emissions performance of a modern coal-fired water-heating and cooking stove using a contextual test sequence that replicates typical patterns of domestic use. Known as a low-pressure boiler, when this stove was fueled with raw coal, the findings indicate that front-loading the fuel, which devolatilizes the new fuel gradually, produced consistently higher space heating efficiency and lower emission factors than top-loading the same stove, which devolatilizes new fuel all at once. Comparing the performance at both high and low power gave the similar results: front-loading with raw coal produced consistently better results than top-loading. The average water heating efficiency when front-loading was (58.6±2.3)% and (53.4±1.8)% for top-loading. Over the sixteen-hour test sequence, front-loading produced 22% lower emissions of PM2.5 (3.9±0.6) mg/MJNET than top-loading (4.7±0.9) mg/MJNET. The same pattern was observed for carbon monoxide and the CO/CO2 ratio. CO was reduced from (5.0±0.4) g/MJNET to (4.1±0.5) g/MJNET. The combustion efficiency (CO/CO2 ratio) improved from (8.2±0.8)% to (6.6±0.6)%. Briquetted semi-coked coal briquettes are promoted as a raw coal substitute, and the tests were replicated using this fuel. Again, the same pattern of improved performance was observed. Front loading produced 3.5% higher heating efficiency, 10% lower CO and a 0.9% lower CO/CO2 ratio. It is concluded that, compared with top loading, the manufacturers recommended front-loading refueling behavior delivered better thermal, emissions and combustion performance under all test conditions with those two fuels. Keywords: stoves, front-loading, top-loading, refueling, domestic coal, thermal efficiency, PM2.5 emissions, semi-coked coal briquettes DOI: 10.25165/j.ijabe.20191203.3880 Citation: Ahmad R, Zhou Y G, Zhao N, Pemberton-Pigott C, Annegarn H J, Sultan M, et al. Impacts of fuel feeding methods on the thermal and emission performance of modern coal burning stoves. Int J Agric & Biol Eng, 2019; 12(3): 160–167.